Characteristics of Surface Tension on First Edible Oil and Frying the Mixed with Candles by Using Torsion Dynamometer - Windarti, Dwi; Najib, M. Faruq; Rakhmadi, Frida Agung (Proceeding International Conference on Science and Engineering, 2019)
Cooking oil pure with the content that has been determined according to the needs that require measurement data minimum and the measurement of the maximum permissibility of the oil it consumed, and the content contained in the oil should have a standard that had been determined by laboratory results that do not interfere with the system of the body when consumed. However, when the pure cooking oil that has been supplemented with other substances or other material that would change the sound into different standard. By way of meeting the data compare surface on pure cooking oil and cooking oil wax mixture. So with this study we can know the difference in surface tension characteristics with Torsion Dynamometer that the elections were not arbitrary and cooking oil consumed well and healthy.